FREEQUNCY OF ESCHERICHIA COLI IN PATIENTS WITH COMMUNITY ACQUIRED URINARY TRACT INFECTION AND THEIR RESISTANCE PATTERN AGAINST SOME COMMONLY USED ANTI BACTERIALS - Ahmad, Waseem; Jamshed, Fareeda; Ahmad, Wajeeha (Journal of Ayub Medical College Abbottabad, 2015)
Background: Urinary tract infection (UTI) is a very common health problem and Escherichia coli (E coli) are the most common organisms associated with community acquired UTI. Unfortunately these bacteria have developed extensive resistance against most of the commonly used anti-bacterials. The objective of this study was to determine the frequency and resistance pattern of E coli in patients of community acquired UTI in an area in northern part of Pakistan. Methods: Urine specimens were collected from patients who were clinically diagnosed as community acquired UTI. Urine routine examination (Urine RE) was done and samples positive for UTI (Pus cells >10/High Power Field) were included in the study. These samples were inoculated on Eosin Methylene Blue (EMB) agar plates and incubated at 37oC for 36 hours. Suspected colonies were then inoculated further on EMB plates for pure cultures of E coli characterized by certain morphological characteristics. IMViC was applied for the confirmation of E coli. In vitro antibiotic susceptibility tests of E coli were performed with standardized commercial susceptibility discs (OXOID). Results: Out of 50 specimens, positive for UTI by urine RE, 20 showed pure growth of E coli on culture (40%). The majority of the isolates (28%; n=14) were from women while only 12% (n=6) were from men. Escherichia coli showed a high rate of resistance towards Ampicillin (90%), Tetracycline (70%), Erythromycin (70%) and Trimethoprim-Sulfamethoxazole (55%). Sparfloxacin showed better results (45%) than ciprofloxacin (50%). Out of 20 E coli isolates, two (10%) were resistant to all the antibacterials except chloramphenicol, eight isolates (40%) showed resistance to six or more than six while 14 (70%) were resistant to four or more than four drugs. Conclusion: Rate of resistance of E coli against commonly used antibacterials was quite high and majority of the strains showed multidrug resistance. Keywords: E coli, Drug resistance, Urinary tract infection